The Influence of Tax Minimization, Debt Covenant, and Exchange Rate on Transfer Pricing in an Islamic Economic Perspective: Study on Transportation and Logistics Companies Listed on the Indonesia Stock Exchange 2021-2023 - Fadia Nazwari; Madnasir Madnasir; Suhendar Suhendar (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2025)
This study examines the influence of tax minimization, debt covenants, and exchange rates on transfer pricing practices among transportation and logistics companies listed on the Indonesia Stock Exchange from 2021 to 2023. Adopting a quantitative approach, the research employs secondary panel data collected from corporate financial reports and the official IDX database. A purposive sampling method was used to select 14 firms, resulting in 42 firm-year observations. Data analysis was conducted using multiple linear regression with MS Excel and IBM SPSS 30. The results show that, individually, tax minimization and debt covenants have no significant effect on transfer pricing, while the exchange rate has a positive but statistically insignificant impact. However, when considered jointly, all three variables exert a significant and positive influence on transfer pricing decisions. From the perspective of Islamic economic law, transfer pricing practices should adhere to the principles of justice (ʿadl), transparency, and truthfulness, while avoiding manipulative behavior that undermines public interest and state revenue. This study offers a normative framework to assess whether prevailing transfer pricing strategies in the logistics sector align with or deviate from the objectives of Islamic law (maqāṣid al-sharīʿah), particularly in terms of financial ethics and distributive equity. The key contribution of this research lies in providing empirical evidence on the determinants of transfer pricing within an Islamic legal-economic framework—an area that remains underexplored in emerging market contexts. Moreover, the findings offer practical implications for fiscal authorities and policymakers in designing tax and financial regulations that not only promote economic efficiency but also uphold Islamic ethical standards and good Sharia governance